The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/la9503919
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopy Study of Sulfonated Polyethylene

Abstract: Detailed X-ray photoelectron spectroscopy analysis of sulfonated high-density polyethylene (HDPE) prepared by using a gaseous mixture of SO3 + N2 was carried out. It was shown that the surface contains, apart from sulfonic acid groups, sulfate, keto, and polyene linkages. The evolution of the different surface groups depends upon the conditions of sulfonation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
1
33
2
Order By: Relevance
“…The carbon peak (C 1 s) is asymmetric, and is deconvoluted into two components: one at 285 eV attributed to CC, CC and CH bonds, whose binding energies are so close that they cannot be resolved, and a second component around 288 eV that corresponds to CO and CS bonds, but mostly CO bonds. The presence of carboxyl species on the surface will give rise to a C 1 s level at 289 eV . In the present study no C 1 s level at 289 eV is observed, pointing to the absence of this species on the surface.…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…The carbon peak (C 1 s) is asymmetric, and is deconvoluted into two components: one at 285 eV attributed to CC, CC and CH bonds, whose binding energies are so close that they cannot be resolved, and a second component around 288 eV that corresponds to CO and CS bonds, but mostly CO bonds. The presence of carboxyl species on the surface will give rise to a C 1 s level at 289 eV . In the present study no C 1 s level at 289 eV is observed, pointing to the absence of this species on the surface.…”
Section: Resultscontrasting
confidence: 44%
“…This means that, in this latter case, the amount of sulfonated groups largely exceeds that of diene units and hence sulfonation cannot be limited to the initial double bonds and must proceed also on the saturated backbone chain of the copolymer precursor by a different mechanism. Ihata and Idage et al proposed that the sulfonation of high‐density polyethylene films with gaseous SO 3 occurs via a radical mechanism and species such as polyethylene radicals, SO 3 H radicals or peroxy radicals could be involved as intermediates . In another investigation Tada and Ito concluded that S atoms may act as an electrophilic centre reacting with negatively charged C atoms of polypropylene through electrophilic addition of SO 3 in a similar way to what happens in aromatic compounds …”
Section: Resultsmentioning
confidence: 96%
“…When the sulfonation time exceeds 3 h, desulfonation reaction seems to be taking place while forming new functional groups containing elemental sulfur and oxygen atoms. It has been suggested that the formation of C¼ ¼C double bonds occurs by the desulfonation reaction following the formation of sulfonic acid [64][65][66] groups. Sulfonic acid bands around 1250-1000 cm À1 region indicate the presence of a weak peak, as a shoulder, located at about 1170 cm À1 (CAC chain stretching þ CH 3 rocking þ CH bending), clearly visible in the spectrum of sulfonated sample at 120 C for 30 min [ Fig.…”
Section: Assessment Of Ft-ir Spectroscopy Datamentioning
confidence: 99%
“…Among polymers, surfaces of polyolefins have a low surface energy and are very inert, and various sulfonation methods have been tried to improve properties such as adhesion and wettability. Sulfonation includes several commonly used methods, e.g., treatments with gaseous SO 3 , [1,2] hot concentrated sulfuric acid, [3][4][5] and fuming sulfuric acid. [6][7][8] In addition, sulfonation using gaseous SO 2 has also been widely used for many years.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] It has been reported that SO 3 reacts with polyethylene films to yield sulfonic acid groups, although several reports on the reaction propose different sulfonation mechanisms. [1][2][3][4][5] We have proposed sulfonation mechanism of LDPE films with fuming sulfuric acid where SO 3 reacts with LDPE films to produce sulfonic acid groups via the formation of sultones. [17] Given that the generation of SO 3 occurs during photosulfonation, there might be a possibility of the production of sulfonic acid groups via the formation of sultones in the reaction between SO 3 and LDPE films.…”
Section: Introductionmentioning
confidence: 99%